SOX2 hypomorphism disrupts development of the prechordal floor and optic cup - Langer, Lee (2012)
Haploinsufficiency for the HMG-box transcription factor SOX2 results in abnormalities of the human ventral forebrain and its derivative structures. These defects include anophthalmia (absence of eye), microphthalmia (small eye) and hypothalamic hamartoma (HH), an overgrowth of the ventral hypothalamus. To determine how Sox2 deficiency affects the morphogenesis of the ventral diencephalon and eye, we generated a Sox2 allelic series (Sox2(IR), Sox2(LP), and Sox2(EGFP)), allowing for the generation of mice that express germline hypomorphic levels (<40%) of SOX2 protein and that faithfully recapitulate SOX2 haploinsufficient human phenotypes. We find that Sox2 hypomorphism significantly disrupts the development of the posterior hypothalamus, resulting in an ectopic protuberance of the prechordal floor, an upregulation of Shh signaling, and abnormal hypothalamic patterning. In the anterior diencephalon, both the optic stalks and optic cups (OC) of Sox2 hypomorphic (Sox2(HYP)) embryos are malformed. Furthermore, Sox2(HYP) eyes exhibit a loss of neural potential and coloboma, a common phenotype in SOX2 haploinsufficient humans that has not been described in a mouse model of SOX2 deficiency. These results establish for the first time that germline Sox2 hypomorphism disrupts the morphogenesis and patterning of the hypothalamus, optic stalk, and the early OC, establishing a model of the development of the abnormalities that are observed in SOX2 haploinsufficient humans.